Exploring the One Health Perspective in Sweden's Policies for Containing Antibiotic Resistance - Jaran Eriksen; Ingeborg Björkman; Marta Röing; Sabiha Y. Essack; Cecilia Stålsby Lundborg (MDPI AG, 2021)
Antibiotic resistance is considered to be a major threat to global health. The main driver of antibiotic resistance is antibiotic use. Antibiotics are used in humans, animals, and food production and are released into the environment. Therefore, it is imperative to include all relevant sectors in the work to contain antibiotic resistance, i.e., a One Health approach. In this study, we aimed to describe and analyse Sweden's policies related to containing antibiotic resistance, from a One Health perspective. Twenty-three key policy documents related to containment of antibiotic resistance in Sweden were selected and analysed according to the policy triangle framework. Sweden started early to introduce policies for containing antibiotic resistance from an international perspective. Systematic measures against antibiotic resistance were implemented in the 1980s, strengthened by the creation of Strama in 1995. The policies involve agencies and organisations from human and veterinary medicine, the environment, and food production. All actors have clear responsibilities in the work to contain antibiotic resistance with a focus on international collaboration, research, and innovation. Sweden aims to be a model country in the work to contain antibiotic resistance and has a strategy for achieving this through international cooperation through various fora, such as the EU, the UN system, and OECD.